2020
DOI: 10.2174/1381612826666200614180958
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism Genes in Stroke Pathogenesis: The Atherosclerosis

Abstract: : Stroke is the second leading cause of death and a major cause of disability worldwide. Both modifiable and non-modifiable risk factors can affect the occurrence of ischemic stroke at varying degrees. Among them, atherosclerosis has been well recognized as one of the main culprits for the rising incidence of stroke-related mortality. Hence, the current review aimed to summarize the prominent role of lipid metabolism genes such as PCSK9, ApoB, ApoA5, ApoC3, ApoE and ABCA1 in mediating ischemic stroke occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…The underlying mechanism of the synergistic interaction is still unclear, but studies have confirmed that atherosclerosis is the leading cause of increased stroke-related mortality [ 36 ]. As a progressive inflammatory disease, atherosclerosis is caused by deposit/plaque accumulation in the intima of blood vessels, which causes arterial narrowing [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of the synergistic interaction is still unclear, but studies have confirmed that atherosclerosis is the leading cause of increased stroke-related mortality [ 36 ]. As a progressive inflammatory disease, atherosclerosis is caused by deposit/plaque accumulation in the intima of blood vessels, which causes arterial narrowing [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism related genes, namely LMRGs, as the second messenger of intracellular signal transduction, lipids behave essential roles in different organelles ( Efeyan et al, 2015 ). Researches about LMRGs were widely conducted in various diseases like degenerative alterations, atherosclerosis, diabetes, and different kinds of cancers ( Santos and Schulze, 2012 ; Johnson and Stolzing, 2019 ; Chow et al, 2020 ; Thongnak et al, 2020 ). Recent years, LMRGs reprogramming has also been regarded as a novel hallmark of tumor malignancy, and the pivotal roles of LMRGs in the initiation, progression, and treatment of tumors have been proved ( Cheng et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is the main clinical type of cerebrovascular disease. Among them, atherosclerosis has been well-recognized as one of the main culprits for the rising incidence of stroke-related mortality [ 2 ]. Plaque rupture and thrombosis result in the acute clinical complications of stroke.…”
Section: Introductionmentioning
confidence: 99%